Pola Asuh Orangtua Dengan Kemandirian Anak - Asti Reswari Dewi; Murtini; Kurniasari Pratiwi (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: Independence in children is very important. Characteristic of independence is children can completetheir own tasks. Based on the current preliminary study, the problems that are often found are there are still childrenwho can not be independent. One of the factors that allegedly influenced independence is parenting style. Parentingconsists of 3 types of authoritarian parenting, permissive, and democratic.Objectives: To know the relationship of parenting style with the independence of preschoolers Kindergarten StateRembang.Method: This research is a kind of research of analytic survey, with cross sectional approach. The population of thisresearch are TK Negeri Rembang students amounted to 110, and sampling method with simple random samplingmethod is 87 respondents. The research instrument used 2 questionnaires namely parenting style questionnaireand preschoolers self-reliance. Analysis using chi square.Results: The most widely adopted parenting style was the democratic parenting style of 54 respondents (72.0%),and the least authoritarian parenting 2 respondents (2.7%). Independence of children 64.0% children independentand not independent 27.0%. Results of analysis with chi square known X2 count <X2 table = 3,986 <5,591 and pvalue 0,136.Conclusion: There is no relationship between parenting style with the independence of preschool children Kindergarten State Rembang.Keywords: parenting style, Independence